STUDENTS' DIFFICULTIES IN UNDERSTANDING ENGLISH AS A FOREIGN LANGUAGE TEXTS (Universitas PGRI Sumatera Barat, 2021)
This study entitled “Students’ Difficulties in Comprehending English as a Foreign Language (EFL) Text” was intended to find out the challenging areas of difficulty in reading comprehension and to find out why the students faced the difficulties in that areas. The participants of this study were the students of XIIPA-3 and there were 26 students of XIIPA-3. The instruments of this study were test, and interview guides. Based on the analysis of the test, the writer found that the challenging areas in comprehending the text were inference, vocabulary and phrase questions and this question also was classified into the difficult question based on index difficulty formula. Through the interview, the writer found that the students are poor in vocabulary mastery, and limited knowledge in analyzing reading comprehension question. Thus, this study found that the three areas above were the challenging parts faced by the students. There were some factors influencing the students’ challenging in comprehending the text. First it was also influenced by their weaknesses in mastering wide range of vocabulary, sentence structure, and reading comprehension question types in English. And the second was lack of knowledge in analyzing the text.